Developing Students’ Autonomy to Resolve a Paradoxical Issue in China’s Secondary School Education - Yu, Haishen; Czerepaniak-Walczak, Maria; Muszyńska, Barbara (INSTED: Interdisciplinary Studies in Education & Society, 2023)
Students’ autonomy in learning is becoming more important in education. An ethnographic research study was conducted on institutional strategies for student autonomy in secondary schools in China, having found a paradoxical issue that is the "quality education" in the curriculum and teaching for testing system in China’s secondary schools. We propose developing students’ autonomy to resolve this paradoxical issue. Schools are applying some strategies in developing students’ autonomy, such as strict schedules and motivating students in learning. Although these strategies may increase students’ willingness to learn to some extent, the drawbacks are obvious. Schools need to adopt other strategies to develop students’ autonomy to a higher level.